Design and development of a portable and adjustable wheelchair ramp - Mohamad Aaqil Mohamad Santosa (Nanyang Technological University, 2020)
Currently, Singapore is facing an aging population. It is not surprising that there will be a greater surge of elderly using more mobility devices such as wheelchairs. Hence, there is a growing need for facilities to include designs that enable the easy accessibility of these mobility devices. Many of Singapore’s public infrastructure including housing estates cater for wheelchair users unlike the structure of most households. Households often have kerbs of varying heights from within which may obstruct the movement of the wheelchair user whenever a kerb is of a challenging height. Therefore, for this project we aim to design and develop a portable and adjustable wheelchair ramp so as to overcome the kerbs of varying heights located primarily within the household. Literature review was being performed on the crucial environmental considerations (doorway widths, household kerb heights, typical wheelchair dimensions and ramp inclination angle) to decide on the Design Requirements which is then used to undergo a Conceptual Design approach using Functional Analysis, Morphological Chart, and finally Decision Matrix. Detailed Design was then performed involving calculations, followed by producing a Computer Aided Design (CAD) model. Finite Element Method (FEM) simulations were then performed to determine if the stresses for our design are acceptable. Finally, a prototype was fabricated for testing and evaluation in order to access its performance and to evaluate for any future improvements. Overall, an adjustable and portable ramp was successfully built to aid wheelchair users to manoeuvre in their households with ease.